DEVELOPMENT STRATEGY FOR THE WARSO UNGGUL GEMILANG BUSINESS USING THE BUSINESS MODEL CANVAS - Ayutyas Sayekti; Selvy Alfionita; Hermawan Wana (Kesatuan Press, 2023)
Warso Unggul Gemilang is an agribusiness specializing in free- range chicken breeding in Bogor Regency, West Java. The demand for Day Old Chickens (DOC) from regions outside Java creates opportunities for Java-based businesses to supply DOC. However, as a medium-scale company, Warso Unggul Gemilang has yet to fully utilize Industry 4.0 advancements for efficiency due to underutilized technology and workforce shortages. Sales primarily depend on WhatsApp, causing inconsistent harvest targets. Recording activities also need more optimal technology. A development strategy using the Business Model Canvas and income statement analysis is required to address these issues for optimal and sustainable results. Digitization involves using Google Forms and Microsoft Excel for recording while marketing is improved through active social media engagement, using Facebook’s marketplace features, Facebook ads, company websites, and marketplaces. The benefits include improved management activities, efficiency, and effectiveness in the competitive landscape. These efforts increased the receipts and the return R/C (return cost) ratio.